1998
DOI: 10.1111/j.1475-2743.1998.tb00602.x
|View full text |Cite
|
Sign up to set email alerts
|

Soil degradation and desertification induced by vegetation removal in a semiarid environment

Abstract: The fragile soils at the transition between semiarid and arid areas are continuously threatened by human activity, which frequently involves the elimination of plant cover. We studied the impact of vegetation removal on soil characteristics in senliarid Mediterranean Spain using two plots (15 m x 5 m), installed on a north facing slope of 23%.Vegetation was removed from one of the plots (disturbed plot), and changes in the soil characteristics were compared with an undisturbed control plot. Fifty-five months a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(38 citation statements)
references
References 15 publications
1
34
0
3
Order By: Relevance
“…The data recording period in this area extends from 1989 until 2003. Results of the studies carried out in this area using this set-up can be found in Castillo et al (1997), Albaladejo et al (1998) and Martínez-Mena et al (2000, 2002.…”
Section: Santomera Area (San)mentioning
confidence: 99%
“…The data recording period in this area extends from 1989 until 2003. Results of the studies carried out in this area using this set-up can be found in Castillo et al (1997), Albaladejo et al (1998) and Martínez-Mena et al (2000, 2002.…”
Section: Santomera Area (San)mentioning
confidence: 99%
“…Human activities have been commonly overestimated when identifying the causes of soil degradation [Lal et al, 1998]. Some researchers have recognized that climatic change leading to less vegetation could result in irreversible soil degradation in semiarid areas [Albaladejo et al, 1998], but they did not give a quantitative assessment. How and to what degree climate change will cause soil degradation at both global and regional scales remains unclear and thus to be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…Chou (1987) reported that only shrubs and grasses could be grown in the arid and semiarid conditions. Albaladejo et al (1998) has observed that the fragile ecosystems at the transition between semiarid and arid areas are not able to recover fully after a severe disruption such as vegetation removal. However, in the central part of Yuanmou, Yunnan Province there is a history of six to eight years of successful reforestation projects (72-77 per cent survival) on areas of approximately 100 ha.…”
Section: Introductionmentioning
confidence: 99%